A therapeutic community training programme for Aotearoa New Zealand. Issue 3 (12th September 2016) - Nelson, Anna
Abstract : Purpose: The purpose of this paper is to explore and develop appropriate responses to the workforce development needs of Aotearoa New Zealand Therapeutic Communities (TC). Design/methodology/approach: Matua Rak i took a workforce development design approach using principles of participatory/co-design. Findings: A scoping exercise undertaken to explore the workforce development needs of Aotearoa New Zealand TC concluded that there was a shortage of addiction practitioners ready, willing and able to work in the TC environment and that a workforce development solution was desired by stakeholders. Following the scoping exercise a demand analysis found that there was a need for a TC training programme to be delivered in the Aotearoa New Zealand context. Outcome: a culturally appropriate TC training programme was developed in consultation with a wide range of stakeholders. The training programme was then piloted with a group of 23 practitioners. Evaluation of participant engagement and satisfaction indicated that the training programme was appropriate to both the needs of the workforce and the TC context. Originality/value: The TC training, developed as a result of this workforce development design approach provides unique content and processes to meet the needs of the TC workforce in the New Zealand context.